IMPLEMENTATION OF THINKING ALOUD PAIR PROBLEM SOLVING MODEL WITH MIND MAP TO INCREASE STUDENT’S ACTIVITIES AND THEIR LEARNING OUTCOME - Evilidia Ketaren (ATRIUM PENDIDIKAN BIOLOGI, 2021)
This research was based on the problem that occur in SMAN 1 Lembah Melintang where the method of learning that applied with the usual discussion method lack influence on learning competencies of students in learning biology. Therefore, researches apply giving homework by making mind map task before cooperative learning with Thinking Aloud Pair Problem Solving type that aims to improve student learning competency through activities and learning outcomes at XII grade of SMAN 1 Lembah Melintang. Sample of this study was taken from XII IPA3 class because compared to other class of XII IPA, the activity and learning achievement were lowest. This research was conducted in two cycles in which each cycle consisted of planning, acting, observing and reflecting. Based on the results of the researcher’s observation on student’s learning activities of eight indicators from the first cycle to the second cycle, there was an improvement on the number of student’s activities in the first cycle were in good category and the second cycle, were in very good category. Student’s learning achievement improved from 57,94% in the first cycle into 85,29% in the second cycle. Based on the result of the research, the researcher concluded that the use cooperative learning Thinking Aloud Pair Problem Solving assisted with mind map task, can improve student’s activities and ther learning achievement as well at XII IPA3 class in SMAN 1 Lembah Melintang.